Charter and Ordinances of the City of Waterbury, Connecticut, with Amendments Thereto: Revised to January 1, 1902 (Waterbury, CT: Mattatuck Press, 1902), 230. Good Order and Decency, § 8. Passed by Board of Aldermen March 15, 1897; Approved March 19, 1897 - (:unkn) unknown (General Publisher, 1897)
The mayor is authorized to issue permits related to the concealed carry of weapons. Licenses are granted on the mayor's judgment "when it is advisable..." The mayor shall have the power to revoke at his pleasure. Permits shall only be valid for one year.
--
Keywords: CARRY - CONCEALED